A prospective descriptive study of evaluation of menstrual disorders in thyroid dysfunction - Kothapalli, Durgavathi; Kolluru, Kamesari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Menstrual irregularities are common with thyroid disorders. It has been reported that hyperthyroidism the most common manifestation is simple oligomenorrhea and hypothyroidism usually is associated with polymenorrhea. Present study has been designed to evaluate the menstrual and endometrial patterns in women with thyroid disorders in costal Andhra Pradesh. Methods: During the study period of two years and ten months we have enrolled 110 patients with clinical presentation of thyroid disorder with menstrual irregularities as per our study criteria. Based on report patients were divided in to three groups, hyperthyroid, hypothyroid and subclinical hypothyroidism. Based on abnormal menstrual pattern patients were divided in to menorrhagia, oligomenorrhea, polymenorrhea, and amenorrhea groups. Endometrial biopsy was taken from women in perimenopausal age group and histopathological examination was done to know the pattern of endometrium. Results: Subclinical hypothyroidism was present in 24 (21.81%) patients, hypothyroidism was present in 52 (47.27%) patients and hyperthyroidism was present in 34 (30.90%) patients. amenorrhea was present in 26 (23.63%) patients, oligomenorrhea was present in 12 (10.90%) patients, Intermenstrual bleeding was present in 2 (1.81%) patients, Menorrhagia was present in 44 (40%) patients which was most common type of menstrual disorder and Polymenorrhagia was present in 26 (23.63%) patients. Conclusions: Hypothyroidism is most common thyroid disorder followed by hyperthyroidism and subclinical hypothyroidism is least common. We have found that menstrual irregularities are more common in hypothyroid patients than hyperthyroid. Menorrhagia and Polymenorrhagia is more common than amenorrhoea and oligomenorrhea in hypothyroid patients.